Model simulation for increased airport capacity via traffic load balancing approach - Wee, Hong Jie (2015)
Flight schedules refer to where and when the airline will operate and such is random and dynamic in nature. Airports worldwide yearn to maximise and optimise their operations with the intention of having as many aircraft movements as possible. One such airport operation to be maximised is the runway throughput, as it directly determines the number of departures and arrivals occurring at a particular airport. As flight schedule deviates daily, it is difficult to predict if the maximum capacity of a runway is achieved, based on the current flight schedules. This report aims to study how flight scheduling will affect Singapore’s Changi Airport’s runway throughput with the use of a fast time simulation software, AirTOp. A model of Singapore’s airspace and airport is correctly built in AirTOp. By utilizing this model, the best routes for arrivals into Singapore from the different entry fixes and an accurate index for assessing the runway capacity can thus be determined by the methodology used. In addition, an optimal ratio of arrivals to departures will also be established. This index is then validated with actual flight status data to assess its accuracy. This report will then discuss on ways to achieve the maximum runway capacity. Lastly, recommendations to better improve the methodology and index will also be suggested in order to increase the robustness and accuracy of the index.